2022
DOI: 10.3390/nu14122456
|View full text |Cite
|
Sign up to set email alerts
|

How Diet and Physical Activity Modulate Gut Microbiota: Evidence, and Perspectives

Abstract: Gut microbiota plays a significant role in the maintenance of physiological homeostasis, contributing to human health. Nevertheless, some factors (sex, age, lifestyle, physical activity, drug-based therapies, diet, etc.) affect its composition and functionality, linked to pathologies and immunological diseases. Concerning diet, it interacts with microorganisms, leading to beneficial or detrimental outcomes for the health of host. On the other hand, physical activity is known to be useful for preventing and, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 103 publications
(94 reference statements)
1
45
0
4
Order By: Relevance
“…An unhealthy diet, rich in processed meat and low in fibers, has been associated with alterations in the gut microbiome and barrier function of the colonic epithelium [ 41 ]. In particular, some evidence indicated that fiber is more effective than the Mediterranean diet on influencing the gut microbiota composition [ 42 , 43 , 44 , 45 , 46 ]. In vivo studies have shown that disruption of the healthy gut microbiota has direct effects on the immune system by triggering a pro-inflammatory environment controlled by specific subpopulations of the immune system (e.g., natural killer cells) [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…An unhealthy diet, rich in processed meat and low in fibers, has been associated with alterations in the gut microbiome and barrier function of the colonic epithelium [ 41 ]. In particular, some evidence indicated that fiber is more effective than the Mediterranean diet on influencing the gut microbiota composition [ 42 , 43 , 44 , 45 , 46 ]. In vivo studies have shown that disruption of the healthy gut microbiota has direct effects on the immune system by triggering a pro-inflammatory environment controlled by specific subpopulations of the immune system (e.g., natural killer cells) [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of ethnicity is not clear because there are many confounding factors or variables that could reduce or increase its weight, like lifestyle (rural vs. urban housing context) [ 20 ], religion [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ], diseases [ 32 , 33 ], and physical activity (high-intensity exercises vs. endurance, sedentary vs. physical activity) [ 32 ]. The most stressful factor is probably diet, as it is well known that diet styles and nutrients directly affect the qualitative and quantitative composition of gut microbiota.…”
Section: Gut Microbiotamentioning
confidence: 99%
“…In addition to the detrimental effects of unhealthy dietary behaviours on physical health, implications for mental health are also evident. Specifically, dietary patterns with high consumption of processed sugars and meats, which are known carcinogens [11,12], and limited fruit and vegetable intake, such as the Standard Western diet, is characterized by local inflammation of the GI tract and increased intestinal permeability [13], and associated with greater incidence and severity of mental health conditions and symptom burden, including depression [14].…”
Section: Diet Exercise and Cancermentioning
confidence: 99%
“…Exercise, and especially diet, have been implicated as important health behaviour factors impacting the human gut microbiota, which consists of the community of microorganisms, notably bacteria, fungi, archaea and eukaryotes, that colonize the gastrointestinal (GI) tract [22]. Previous studies with rodents and humans using randomized controlled trials and observational designs, have shown that regular exercise can impact the composition of the gut microbiota [6,13]. Furthermore, several recent, comprehensive reviews drawing on clinical and preclinical evidence have detailed how specific dietary behaviours, such as the Mediterranean diet, can impact the gut microbiota [13,23,24].…”
Section: Diet Exercise and Cancermentioning
confidence: 99%